2022
DOI: 10.3389/fneur.2022.831899
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Roles of Family Resilience and Social Support in the Relationship Between Illness Severity and Depressive Symptoms Among Primary Caregivers of Children With Epilepsy in China

Abstract: PurposeThis study was designed to assess the effects of epilepsy severity, family resilience, and social support on depression in primary caregivers of children with epilepsy (CWE), and to test the mediating roles of family resilience and social support in this relationship.MethodTwo hundred fifty-two caregivers of children with epilepsy were recruited from October 2020 to May 2021. The questionnaire contained sociodemographic characteristics, Epilepsy Severity, Chinese-Family Resilience Assessment Scale (C-FR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Moreover, this psychological distress was detrimental to the health-related quality of life of family members and family system ( 40 ), which was not conducive to the family resilience. However, when the levels of family resilience was high, it could promote the mobilization of social resources, which further reduced family members’ negative emotions and improved parental mental health ( 41 ). Given that the parents’ depression was a predictor for family resilience, this finding highlights the importance of screening the psychological distress and developing interventions to reduce depression among parents of CWE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this psychological distress was detrimental to the health-related quality of life of family members and family system ( 40 ), which was not conducive to the family resilience. However, when the levels of family resilience was high, it could promote the mobilization of social resources, which further reduced family members’ negative emotions and improved parental mental health ( 41 ). Given that the parents’ depression was a predictor for family resilience, this finding highlights the importance of screening the psychological distress and developing interventions to reduce depression among parents of CWE.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to thank all the caregivers involved in this study. In addition, what we need to acknowledge is that portions of this data were previously presented at Frontiers in Neurology ( 41 ).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Our findings also support that adequate social support promotes family resilience. Quantitative studies have found that positive social interactions are positively associated with family resilience (Khatib et al, 2022), possibly because families who reported greater support received in positive social interactions would find relief from negative emotions (Wei et al, 2022) and more resources to cope with the challenges of illness (Karadag et al, 2013). The sharing of experiences among the parents in the hospital was regarded as an essential source of support.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy is a chronic disease of sudden abnormal discharge of brain neurons, resulting in temporary brain dysfunction (Xu et al, 2022). The annual prevalence of active epilepsy with seizures is 4.6% (Wei et al, 2022). Globally, there are 5-6-million active epilepsy patients, with about 400,000 new epilepsy patients added annually (Liang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%